Factors associated with smartphone addiction: A comparative study between Japanese and Thai high school students - Arunrat Tangmunkongvorakul (2020)
© 2020 Tangmunkongvorakul et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background Smartphone addiction is a growing social problem with adverse health outcomes. There are few comparative studies in Asia that examine factors associated with smartphone addiction. The current study aimed to address this research gap by presenting a comparative analysis of factors associated with smartphone addiction in Japan and Thailand, two countries heterogeneous in both their level of economic development and culture. Methods Participant data were collected using two population-based surveys. Participants were high school students in grade 11, aged 16–17 years old, and were selected using quota sampling in Japan in 2014 and random sampling in Thailand in 2016. The outcome of interest was smartphone addiction, measured using a modified version of the Young Diagnostic Questionnaire for Internet Addiction. Multiple logistic regression analysis was performed to determine factors associated with smartphone addiction (gender; nationality; family connectedness; and average time spent on smartphone per day). Results This study included a total of 7694 students, 6585 students from Japan and 1109 students from Thailand. The prevalence of smartphone addiction was 35.9% among Thai students and 12% among Japanese students. Thai students were more likely to have smartphone addiction than Japanese students (AOR 2.76; 95% CI: 2.37–3.30). Being female was associated with increased odds of smartphone addiction in both Japanese (AOR 1.53; 95% CI: 1.32–1.78) and Thai students (AOR 1.34; 95% CI: 1.01–1.78). The parental connectedness variables “my parents noticed when I was unhappy” (AOR 0.77; 95% CI: 0.62–0.96) and “my parents noticed when I did something good” (AOR 0.78, 95% CI: 0.61–0.99) were associated with lower odds of smartphone addiction among Japanese students. Conclusion Smartphone addiction was more prevalent among Thai adolescents than Japanese adolescents, and more prevalent among females than males in both countries. Interventions for reducing smartphone addiction should take into account both context and gender, and should leverage the protective effect of parental connectedness.